Quality Of SMK E Rapor System Version 7.0.0 Using Webqual 4.0 Method At SMKS Manggala Tangerang City - sari, Nurmala; kristiana, Titin (JURNAL TEKNIK KOMPUTER AMIK BSI, 2025)
SMK Manggala Tangerang City is one of the schools that implements an independent curriculum and has implemented the e-Rapor application to process grades and print student report cards since the odd semester of the 2022/2023 Academic Year until now. The eRapor application has been implemented at SMK Manggala and is accessed by all teachers, homeroom teachers, and administrators both online and offline. Currently, the eRapor Application used by SMK Manggala is an eRapor Application with Version 7.0.0. One of the innovations launched by the Directorate of Vocational High Schools, Ministry of Education, Culture, Research and Technology to support the Independent Curriculum is eReport.